Association of coagulation-related indicators with postoperative venous thromboembolism occurrence in patients with pituitary tumors - Yi Xiang; Ya Wu; Huan Liu; Zheng Chen; JinYu Pan (Scientific Reports)
Abstract This study aimed to analyze risk factors for postoperative VTE in pituitary tumor resection patients, focusing on coagulation indicators and their predictive value. This study collected clinical data from 300 patients who underwent pituitary adenoma resection from January 2021 to August 2023 in the Department of Neurosurgery, the Second Clinical College of the Army Medical University, China. Logistic regression modeling was used to identify risk factors for VTE. Restricted cubic spline curves were used to characterize the dose-response relationship between coagulation-related indicators and the risk of venous thromboembolism. The area under the curve (AUC) was calculated using the receiver operating characteristic (ROC) curve to evaluate the predictive power of coagulation-related indicators. Multivariate analysis showed that D-dimer, platelet count and hemoglobin (Hb) were significant predictors of VTE with OR (95% CI) of 1.967 (1.441–2.808), 1.020 (1.013–1.029), and 0.952 (0.914–0.994), respectively. The AUCs for D-dimer, Platelet Count, and Hb were 0.708, 0.731, and 0.712, respectively. The AUC for combining the three coagulation indices was the largest, 0.838. The combined use of D-dimer, Hb, and platelet count can identify high-risk patients early, enabling timely implementation of antithrombotic strategies.